A review of pragmatic and sociolinguistic aspects of language use in English TV shows - Dalal Khamees Qasim; Ali Hasan Ali (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2026)
English television shows have become a ubiquitous source of authentic language input for learners and a rich dataset for researchers investigating real-world language use. This review synthesizes recent studies on the pragmatic and sociolinguistic aspects of language in English TV shows with particular attention to their implications for applied linguistics and language pedagogy. The review examines peer-reviewed journal articles, books and conference proceedings published between 2000 and 2025, using thematic analysis to identify patterns, benefits, challenges and research gaps. Key findings indicate that television dialogue abundantly represents pragmatic features such as speech acts (requests, apologies, refusals, compliments), politeness strategies, conversational implicature, idiomatic expressions and turn-taking mechanisms. Additionally, sociolinguistic dimensions including dialectal variation, social class markers, gender differences, age-related variation and context-driven style-shifting are systematically portrayed. While television dialogue shares many features with natural conversation, it also exhibits stylized characteristics such as reduced overlap, clearer turn boundaries less repetition and raising questions about authenticity. Pedagogically, English TV shows can develop learners' pragmatic competence, enhance sociolinguistic awareness, teach formulaic language, improve listening comprehension and increase motivation. However, the literature has notable limitations including small sample sizes, a bias toward American and British sitcoms, insufficient attention to sociocultural context, a lack of longitudinal studies and methodological inconsistencies. The review identifies future research priorities: longitudinal designs, cross-cultural studies, equity and accessibility, ethical considerations, teacher-AI interaction, diversification of genres and English varieties, learner individual differences, transfer to production and comparative studies across media. In conclusion, English television shows represent a valuable resource for understanding and teaching language in its social contexts, but they should complement rather than replace teachers, direct instruction and authentic interaction. This review provides a comprehensive framework for researchers and educators seeking to integrate televised language into applied linguistics research and language teaching practice.